Quality variation of turmeric during polishing in a power operated turmeric polisher: Quality variation of turmeric during polishing - Jayashree, E; Basheer , Nejma (Journal of Spices and Aromatic Crops, 2022)
Polishing of turmeric is an important post harvest operation done after drying to improve the surface colour and to obtain a smooth surface finish. Turmeric (variety IISR Prathiba) was cleaned and cured for 1 h in a steam operated turmeric boiler and one batch was dried in a solar tunnel drier of size 9 m × 4 m × 2.6 m and the other batch was sun dried on cemented concrete floor until constant weight was obtained. The turmeric obtained by both the methods were subjected to polishing in a power operated turmeric polisher to obtain clean and yellow coloured turmeric. Based on the physical appearance and surface finish, it was revealed that turmeric polished for 30 min was optimum to obtain turmeric rhizomes of marketable acceptance and the degree of polishing for solar tunnel dried turmeric was 5.45% and for sun dried turmeric it was 5.20%.